Exact boundary controllability for a series of membranes elastically connected - Bastos, Waldemar D. [UNESP]; Nunes, Ruikson S. O.; Pitot, João Manoel Soriano [UNESP] (My University, 2017)
In this article we study the exact controllability with Neumann boundary controls for a system of linear wave equations coupled in parallel by lower order terms on piecewise smooth domains of the plane. We obtain square integrable controls for initial state with finite energy and time of controllability near the optimal value.
Keywords: Boundary control; Coupled wave equations; Exact controllability; Neumann control